Review of Recent Laser Technology of Development Multi Qubit Gates Using Ion Trap Method - Al-Temimi, Mohammed; Atiya, Abdulkader H. (Applied mechanics and materials, 2023)
The qubit technology using Trapped ions are taking the systems for practical quantum computing (QC). The normal requirements to achieve quantum supremacy have all been studied with ions, and quantum algorithms use ion-qubit systems have been implemented. I cover in this study many points regarding the concept of Qubit through Ion Trap, near application, and experiments also explore the Multi gates, Hybrid gates implementations